Banjar Language Shifting in Ecolinguistics Perspective - Imam Hendra Saputra; Ninuk Krismanti; Agustina Lestary (Jurnal Lingua Idea, 2021)
The research attempts to examine language shifts that occur in the Banjar community using an ecolinguistics approach. The language shifts studied were limited to the vocabulary shift commonly used in the social interactions of everyday Banjar people. The data gathering was using interviewing and documentation techniques. Interviews are semi-structured interviews. The interview was on respondents spread across various cities in South Kalimantan, where the Banjar language is the language of community communication. Due to the pandemic, researchers enlisted the help of students in their respective hometowns to collect data with protocols that the research team had established. The data was the subject of reduction, organized by category of word classes and reasons for shifts, analysed based on the three-dimensional social theory of language praxis. The three practical social dimensions of language are the ideological, social, and biological dimensions. The research expects to be a reference for Banjar language participation efforts.